2014
DOI: 10.5771/0943-7444-2014-4-276
|View full text |Cite
|
Sign up to set email alerts
|

The Network Pattern of Journal Knowledge Transfer in Library and Information Science in China

Abstract: She teaches knowledge management at the School of Information Management of Wuhan. Her research interests are knowledge management, informetrics and scientific evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Generally considered as the indictor of knowledge flow, citations are often adopted to examine patterns of dynamic disciplinary knowledge production and diffusion (Cronin & Meho, ; Kiss, Broom, Craze, & Rafols, ; Levitt, Thelwall, & Oppenheim, ; Yan & Yu, ; Zhao & Wu, ). Using citation analysis, studies have found that scientific works in one discipline tended to cite publications from adjacent disciplines (van Leeuwen & Tijssen, ) and citations to publications of their own discipline occurred sooner than citations to papers in other disciplines (Rinia, Van Leeuwen, Bruins, Van Vuren, & Van Raan, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally considered as the indictor of knowledge flow, citations are often adopted to examine patterns of dynamic disciplinary knowledge production and diffusion (Cronin & Meho, ; Kiss, Broom, Craze, & Rafols, ; Levitt, Thelwall, & Oppenheim, ; Yan & Yu, ; Zhao & Wu, ). Using citation analysis, studies have found that scientific works in one discipline tended to cite publications from adjacent disciplines (van Leeuwen & Tijssen, ) and citations to publications of their own discipline occurred sooner than citations to papers in other disciplines (Rinia, Van Leeuwen, Bruins, Van Vuren, & Van Raan, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using citation analysis, studies have found that scientific works in one discipline tended to cite publications from adjacent disciplines (van Leeuwen & Tijssen, ) and citations to publications of their own discipline occurred sooner than citations to papers in other disciplines (Rinia, Van Leeuwen, Bruins, Van Vuren, & Van Raan, ). When looking at specific areas of research, it is found that a few library and information science journals heavily cited communication science journals (Borgman & Rice, ) and journal knowledge flows in library and information science is frequent (Zhao & Wu, ). Similarly, Leydesdorff and Probst () revealed that communication science journals have a strong connection with political science and social psychology journals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to four blocks (i.e., macroscopic management and policy, technology management, system engineering, and management science) being generalized, this study has also investigated the evolutional change of four blocks and their member journals. Zhao and Wu (2014) employed structural equivalence to classify 16 LIS journals selected from CSSCI into four blocks in 2003-2007 and 2008-2012, respectively, as follows: a core block, a strong edge block, a weak edge block and a periphery block. In addition to examining the evolutional change over two periods, the core-periphery structure was also identified in this study.…”
Section: Structural Equivalence In a Library And Information Science mentioning
confidence: 99%
“…At the journal level, it is found that knowledge flows in library and information science are frequent (Zhao & Wu, 2014) and a few library and information science journals heavily cited communication science journals (Borgman & Rice, 1992). Because paper citations can be aggregated into several higher levels, studies have explored journal-, institution-, and field-level knowledge flows via journal citations, institution citations, and field citations.…”
Section: Paper Citations and Knowledge Flowsmentioning
confidence: 99%